2002
DOI: 10.1183/09031936.02.00063102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical ventilation on diaphragm function and biology

Abstract: The pathophysiological mechanisms of weaning from mechanical ventilation are not fully known, but there is accumulating evidence that mechanical ventilation induces inspiratory muscle dysfunction.Recently, several animal models have provided potential mechanisms for mechanical ventilation-induced effects on muscle function. In patients, weaning difficulties are associated with inspiratory muscle weakness and reduced endurance capacity. Animal studies demonstrated that diaphragm force was already decreased afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 45 publications
3
52
1
6
Order By: Relevance
“…Although controversy exists, it has been predicted that depressed strength and endurance of respiratory muscles can play a key role in weaning difficulties (26,34,115). However, direct evidence demonstrating cause and effect that VIDD is primarily responsible for weaning problems is lacking due to the difficulty of performing these experiments in humans.…”
Section: Contribution Of Vidd To Weaning Failurementioning
confidence: 99%
“…Although controversy exists, it has been predicted that depressed strength and endurance of respiratory muscles can play a key role in weaning difficulties (26,34,115). However, direct evidence demonstrating cause and effect that VIDD is primarily responsible for weaning problems is lacking due to the difficulty of performing these experiments in humans.…”
Section: Contribution Of Vidd To Weaning Failurementioning
confidence: 99%
“…The techniques used to alter tissue load are extremely diverse but can be separated into two categories based on their effect: decreased muscle activity (DMA) and increased muscle activity (IMA). Examples of DMA are reduced electrical activity through spinal cord isolation and the use of neurotoxins, spinal cord injury or transection, unloading (mainly of the hindlimb), immobilisation of muscle in a shortened position, space flight, mechanical ventilation and bed rest (Carlson et al, 1999;Gayan-Ramirez and Decramer, 2002;Lalani et al, 2000;Talmadge, 2000;Wehling et al, 2000). Examples of IMA are endurance (swim) training and chronic low-frequency stimulation of muscles (CLFS) (De Graaf et al, 1990;Kraus and Pette, 1997;Pette, 1998;Siu et al, 2004;Walker et al, 2004).…”
Section: Gene Expression Levelsmentioning
confidence: 99%
“…The level of this strength reduction is related to duration of MV (Chang, Boots, Brown, et al, 2005;Powers et al, 2002;Sassoon, Caiozzo et al, 2002;Sprague & Hopkins, 2003) and has been reported as one of the major determinants of weaning failure in patients receiving MV (N Ambrosino, 2005;Gayan-Ramirez & Decramer, 2002). Anzueto et al (Anzueto, et al, 1997) observed a transdiaphragmatic pressure reduction of 45% in rats after 11 days of controlled MV.…”
Section: Respiratory Muscle Trainingmentioning
confidence: 99%